Nitrogen-doped graphene quantum dots decorated graphite foam as ultra-high active free-standing electrode for electrochemical hydrogen evolution and phenol degradation - Guo, X.; Zhu, Y.; Han, W.; Fan, X.; Li, Y.; Zhang, F.; Zhang, G.; Peng, W.; Wang, Shaobin (Pergamon, 2018)
© 2018 Elsevier Ltd In this study, nitrogen-doped graphene quantum dots (N-GQDs, ~5 nm) were synthesized and supported on graphite foam (GF) by a facile hydrothermal route. The obtained N-GQDs/GF composite demonstrates as an ultra-active free-standing electrode for electrochemical hydrogen evolution and activation of peroxymonosulfate to degrade phenol pollutant. An overpotential in the electrochemical hydrogen evolution is only -72 mV vs. RHE at 10 mA/cm 2 with a Tafel slope of 84 mV/Dec. The N-GQDs/GF electrode can also achieve 100% phenol removal in short time in electrochemical degradation.